(untitled) (Research, Society and Development, 2021)
This study aims to discuss the importance of operative groups, based on social work, in a group of elderly people who live and live in a nursing home. This study, derived from a Course Conclusion Work, aims to contemplate the knowledge process experienced during the curricular internship, and for this, it was divided into chapters. The first makes a historical review of old age through time, how it is seen by different societies, also bringing the elderly care policies and how these have been implemented in the social context. It highlights the growth in the number of geriatric homes due to the growing aging process and in particular the asylum institution Asilo da Velhice Nossa Senhora Medianeira and its historical trajectory. The second chapter highlights the groups and their meaning in society in a broader way, focusing on operative groups that were the groups developed with the elderly in the nursing home. It also brings the importance of the development of these groups in the third age and what changes make possible the elderly participant. In the third chapter, considerations are made about the Social Work work process, bringing the internship experience from observation to the implementation of the intervention project, emphasizing the final product, obtained through this work process. The methodology of this qualitative study is delineated from a case study, using the logbook as a data collection instrument, in this study we titled it as “field diary”, which were later discussed and related to the pertinent bibliography. With this, it was possible to identify the need for work aimed at the institution’s elderly through the application of operative groups, as well as evaluating this work process positively, with the effectiveness of the group, which results in the strengthening and autonomy of its participants.